Plan de negocios para los servicios de hotelería, restauración y recreación de la estación experimental el Padmi - Quinde Quinde, Daniela Soledad (2022)
Ecuador, the country of the four worlds, has majesty and biodiversity in every corner of the country, which is the key to tourism. These same reasons make it an ideal country to promote the development of it’s tourism, and inspire economic, ethnographic, natural and cultural growth. The south east of Ecuador is surrounded by characterized by these factors. This is location of the province of Zamora Chinchipe, the Yantzaza Canton, and the Los Encuentros parish, where tourism as such is an activity that is not very advanced, which is why it was proposed to carry out a "BUSINESS PLAN FOR HOTEL, RESTAURANT AND RECREATION SERVICES OF THE EL PADMI EXPERIMENTAL STATION IN THE LOS ENCUENTROS PARISH OF THE CANTON YANTZAZA, PROVINCE OF ZAMORA CHINCHIPE". For the development of the research, the general objective was to prepare a business plan for the hotel, restaurant and recreation services of the El Padmi Experimental Station, for which three specific objectives were proposed: Carry out a tourist diagnosis for the implementation of the aforementioned services, in which the internal and external situation of the Station was known. Raise the proposal to implement the services, in which the human talent plan and the marketing plan are established. With the third objective, it was proposed to develop the operability for the Station’s Hotel, restaurant and recreation services, with the previously made proposal of the services to be implemented in the station, it is necessary to carry out a financial plan which does not indicate that the project with a net present value of $ 1,104,990 dollars and an internal rate of return of 259.83% is totally profitable since it will work directly with profits. All the work is developed using the application of technological tools, human resources, biosafety materials and analytical, descriptive, deductive, inductive and bibliographic methodology; in addition to direct observation techniques, surveys and interviews, sample size of the study area and methodology of Karen Weinberger, Carla Ricaurte and their application of summary sheets proposed by MINTUR, Evaluation Matrix of Internal and External Factors. Finally, conclusions are drawn based on the proposed objectives where the feasibility of the project is determined, and the recommendations made to those directly and indirectly with the Padmi Experimental Station.